Role of the CaV1.2 distal carboxy terminus in the regulation of L-type current - Felipe Arancibia; Daniela De Giorgis; Franco Medina; Tamara Hermosilla; Felipe Simon; Diego Varela (Channels)
L-type calcium channels are essential for the excitation-contraction coupling in cardiac muscle. The CaV1.2 channel is the most predominant isoform in the ventricle which consists of a multi-subunit membrane complex that includes the CaV1.2 pore-forming subunit and auxiliary subunits like CaVα2δ and CaVβ2b. The CaV1.2 channel’s C-terminus undergoes proteolytic cleavage, and the distal C-terminal domain (DCtermD) associates with the channel core through two domains known as proximal and distal C-terminal regulatory domain (PCRD and DCRD, respectively). The interaction between the DCtermD and the remaining C-terminus reduces the channel activity and modifies voltage- and calcium-dependent inactivation mechanisms, leading to an autoinhibitory effect. In this study, we investigate how the interaction between DCRD and PCRD affects the inactivation processes and CaV1.2 activity. We expressed a 14-amino acid peptide miming the DCRD-PCRD interaction sequence in both heterologous systems and cardiomyocytes. Our results show that overexpression of this small peptide can displace the DCtermD and replicate the effects of the entire DCtermD on voltage-dependent inactivation and channel inhibition. However, the effect on calcium-dependent inactivation requires the full DCtermD and is prevented by overexpression of calmodulin. In conclusion, our results suggest that the interaction between DCRD and PCRD is sufficient to bring about the current inhibition and alter the voltage-dependent inactivation, possibly in an allosteric manner. Additionally, our data suggest that the DCtermD competitively modifies the calcium-dependent mechanism. The identified peptide sequence provides a valuable tool for further dissecting the molecular mechanisms that regulate L-type calcium channels’ basal activity in cardiomyocytes.